Early Detection of HIV (Human Immunodeficiency Virus) using Immunochromatography Method in Adolescents in Bontovillage Bulaeng - Tiana, Kasratul; Aryandi, Rahmat; Muriyati , Muriyati (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2023)
Background: Human immunodeficiency virus (HIV) is a virus that weakens the human immune system, making people with the virus unable to fight various diseases that attack their bodies. Di sisi lain, Acquired Immunodeficiency Syndromes (AIDS) are symptoms that result from HIV infection that weakens the human immune system. Symptoms resulting from a weakening of the Human Immune System caused by HIV infection. The causes of Human Immunodeficiency Virus (HIV) are sexual intercourse, use of non-sterile syringes among drug users, use of piercings or tattoos, blood transfusions containing the HIV virus. Aim: The aim of the research is to determine the results of early detection of HIV (Human Immunodeficiency Virus) using the immunochromatography method in adolescents in BontoBulaeng Village. Method: This research method is descriptive research. This research was preceded by administering a questionnaire to obtain criteria in accordance with the research, HIV testing was carried out on adolescents using the immunochromatography method. This research began by giving questionnaires to respondents to obtain criteria that were appropriate to the research. Data analysis in this study used the SPSS frequency descriptive statistical test. Result: The results of this research were HIV tests on 30 teenagers, negative results were obtained (100%). Conclusion: Early detection of HIV using the immunochromatography method in adolescents in Bonto Bulaeng Village showed negative results for 30 samples (100%). Keywords: HIV, Teenager, Immunochromatografi